(untitled) (Scientific journal of the Fergana State University, 2026)
This article identifies changes in the climate of North Fergana under the conditions of global climate change. This was determined using the observation data of the Namangan meteorological station on the average annual air temperature and annual precipitation for the last 34 years (1990-2023). Based on the data on the average annual air temperature and annual precipitation, chronological graphs were drawn, and the annual temperature change rate (trend) was determined based on these graphs. In addition, in order to study the process of changing the natural moisture content of North Fergana soils under climate change, maps were prepared in the ArgGis program using images of the Landsat-8 satellite in 1990, 2005 and 2023 and the changes in them were analyzed.